Effect of Zinc Supplementation on Body Composition of Duchenne Muscular Dystrophy Patients: A Quasi-Experimental Study - Thais A. Cunha; Karina M. Vermeulen-Serpa; Evellyn C. Grilo; Mário E. T. Dourado-Júnior; Breno G. P. Bezerra; Núbia R. S. M. Torres; Márcia M. G. D. Lopes; Lucia Leite-Lais; José Brandão-Neto; Sancha H. L. Vale (Journal of Nutrition and Metabolism)
Background. The study hypothesized that zinc supplementation would increase or preserve lean body mass in Duchenne muscular dystrophy (DMD) patients. Therefore, we aimed to evaluate the body composition of DMD patients before and after zinc supplementation. Materials and Methods. The study is a clinical trial comprising 21 boys diagnosed with DMD. Dietary intake parameters were evaluated before zinc supplementation. Serum zinc levels, anthropometry, and body composition were measured in three moments, four months apart. The patients received 5, 10, or 15 mg of zinc bis-glycine supplementation according to age as an oral solution daily for four months. The sample was distributed into two groups according to serum zinc status: zinc deficiency (G1) or adequate zinc (G2). Results. There was a significant difference in lean body mass between the groups: zinc deficiency (G1) or adequate zinc (G2), at three times (p=0.041, 0.016, and 0.009, respectively). After oral zinc supplementation, serum zinc levels were not different between groups. We did not observe differences when associating the parameters between times and groups. Conclusion. Zinc supplementation was able to maintain lean body mass and fat mass in patients with DMD with previous deficiencies. Therefore, it is necessary to have a prior screening of serum zinc levels to observe changes after supplementation.